Using social network analysis in the classroom : a case study applying nodeXL - Kuz, Antonieta
The interest in social networks has extended to different disciplines, such as Computer Science. This approach brings Social Network Analysis (SNA) as the study of social structure in different environments, like companies, establishment, and schools, among others. For this reason, this article highlights basic network information like graphs using actors and relations and important concepts related to classroom like structure which constitutes it. Therefore, the main aim of this research is to examine the educational use of SNA. Furthermore, schools in society are a system of actors joined by relationships. Accordingly, the current paper presents a qualitative analysis through a practical approach of SNA, by describing the classroom as a sociometric experiment using NodeXL, to verify the contrast keeping attention in show how students make informal contact and the knowledge that this brings.